2022
DOI: 10.1536/ihj.22-132
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Left Ventricular Dilatation and Hypertrophy from Electrocardiograms Using Deep Learning

Abstract: Left ventricular dilatation (LVD) and left ventricular hypertrophy (LVH) are risk factors for heart failure, and their detection improves heart failure screening. This study aimed to investigate the ability of deep learning to detect LVD and LVH from a 12-lead electrocardiogram (ECG). Using ECG and echocardiographic data, we developed deep learning and machine learning models to detect LVD and LVH. We also examined conventional ECG criteria for the diagnosis of LVH. We calculated the area under the receiver op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…For example, the LVH of 1120 inpatients in China was predicted using a deep learning model of a convolution neural network. However, the AUC was only 0.62 (with a sensitivity of 68% and specificity of 57%), which is still insufficient 29 . Moreover, as most models lack demographic data and other cardiovascular risk factors, diagnostic efficiency has not improved 30 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the LVH of 1120 inpatients in China was predicted using a deep learning model of a convolution neural network. However, the AUC was only 0.62 (with a sensitivity of 68% and specificity of 57%), which is still insufficient 29 . Moreover, as most models lack demographic data and other cardiovascular risk factors, diagnostic efficiency has not improved 30 .…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39] Analysis of ECG waveforms provides a rapid, easy-to-implement, and cost-effective application for artificial intelligence. Its use in adults has been wideranging, including prediction of ventricular dysfunction, [3][4][5][6][7] ventricular hypertrophy, 8-10 ventricular dilation, 9,11 atrial fibrillation and other arrhythmias, 17,26,40,41 and age, 42,43 sex, 42 and time to death. 8,43 Our findings provide proof-ofconcept evidence that similar ECG applications can be explored in children and suggest that deep learning may also be applicable to other data streams (eg, wearable biosensor data) that could aid in predicting outcomes for children 44 similar to what has been performed in adults.…”
Section: Clinical Significance and Implicationsmentioning
confidence: 99%
“…This has historically motivated the development of computer-generated interpretations on the basis of predefined rules and feature recognition algorithms that may not capture subtleties of an ECG. 2 Recent work has demonstrated that deep learning-based artificial intelligence-enhanced ECG (AI-ECG) algorithms may result in greater diagnostic fidelity; studies of this approach in adult populations have reliably predicted a range of adult cardiovascular phenotypes, including ventricular dysfunction, [3][4][5][6][7] ventricular hypertrophy, [8][9][10] and ventricular dilation. 9,11 Progressive anatomic and physiological changes occurring from birth to adolescence lead to agedependent variations in pediatric ECGs.…”
mentioning
confidence: 99%
See 2 more Smart Citations